2016
DOI: 10.1111/jocd.12224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vitamin D receptors in alopecia areata and androgenetic alopecia

Abstract: This study suggests an important role for VDR in the pathogenesis of AA and AGA through documenting lower serum and tissue VDR levels in AA and AGA patients in comparison with controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
3
36
0
1
Order By: Relevance
“…Fawzi et al have shown that there is decreased expression of tissue and serum VDR by ELISA in patients of AA, and androgenetic alopecia as compared to controls; they also found a negative correlation of tissue VDR and extent of AA. In our study, also, we did not find any correlation between extent of AA and VDR expression in lesional tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Fawzi et al have shown that there is decreased expression of tissue and serum VDR by ELISA in patients of AA, and androgenetic alopecia as compared to controls; they also found a negative correlation of tissue VDR and extent of AA. In our study, also, we did not find any correlation between extent of AA and VDR expression in lesional tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Some have specifically examined the role of the VDR. Fawzi et al recently found lower levels of the VDR in serum and scalp tissue samples in AA patients compared to controls [42]. Polymorphisms of the VDR gene have been shown to increase susceptibility to other autoimmune diseases, including Graves’ disease and psoriasis [45, 46].…”
Section: Micronutrientsmentioning
confidence: 99%
“…reported significantly decreased serum ferritin and serum vitamin D 2 levels in 80 women with either chronic telogen effluvium or FPHL compared to 40 age‐matched healthy females. Fawzi et al . observed decreased serum and tissue levels of vitamin D receptors (VDRs) in 20 patients with AGA.…”
Section: Aetiologymentioning
confidence: 99%